THE RELATIONSHIP BETWEEN ACADEMIC STRESS LEVELS AND BURNOUT AMONG FINAL-YEAR ANESTHESIOLOGY STUDENTS - vania salsabila; Aisyah Nur Azizah; Astika Nur Rohmah (Keperawatan Anestesiologi Program Sarjana Terapan, 2026)
Background: Final-year students in health sciences education face complex academic demands, including the completion of final projects, clinical practice, Objective Structured Clinical Examinations (OSCEs), and competency examinations. These responsibilities often contribute to academic stress, particularly among Anesthesiology Nursing students who carry substantial clinical responsibilities and are directly involved in anesthesia procedures in operating rooms. If not properly managed, academic stress may develop into burnout, a condition characterized by emotional exhaustion, cynicism, and reduced academic effectiveness resulting from chronic stress. Methods: This study employed a descriptive correlational design with a cross-sectional approach. A total of 60 respondents were selected using stratified random sampling. Data were analyzed using the Spearman rank correlation test. Results: The findings revealed that the majority of final-year Anesthesiology Nursing students experienced a moderate level of academic stress (51 students; 85%), while 6 students (10%) experienced high academic stress. Regarding burnout, most respondents were categorized as having moderate burnout (22 students; 36.7%), followed by low burnout (19 students; 31.7%), very low burnout (18 students; 30.0%), and high burnout (1 student; 1.7%). Statistical analysis showed a significant positive correlation between academic stress and burnout (p = 0.000), with a moderate correlation coefficient (r = 0.484). Conclusion: There is a significant positive relationship between academic stress levels and burnout among final-year anesthesiology students. The strength of the relationship was moderate, indicating that higher levels of academic stress were associated with higher levels of burnout.